The effect of acute mental stress on limb vasodilation is unrelated to total peripheral resistance - Paine, Nicola J.; Ring, Christopher; Bosch, Jos A.; McIntyre, David; Veldhuijzen van Zanten, Jet J. C. S. (Psychophysiology, 2013)
Mental stress can trigger myocardial infarction, with poor vascular responses to stress implicated as a pathway. Vascular stress reactivity can be assessed by different methods, such as total peripheral resistance (TPR) and forearm blood flow (FBF). Little is known about how these vascular assessments are linked. This was examined in two separate studies. Healthy men (Study 1: N = 29, Study 2: N = 23) completed rest and mental arithmetic (Study 1: 8 min, Study 2: 16 min). In both studies, heart rate, mean arterial pressure, and FBF increased in response to stress. In Study 1, no changes in TPR were seen, but Study 2 found stress-induced increases in TPR. FBF was not linked to TPR at any time (all ps > .05). It appears that limb vasculature and TPR responses to stress do not give the same information about impairments of the vasculature. These findings are relevant to the interpretation of prior research findings and the design of future studies on stress and vascular responses.
Gesehen am 31.03.2022